Effect of Temperature, Food Quality, Breeding Periods (Time) and Overlap Factors Affecting the Propagation of Varicose Veins - Al Fittouri, Abdulrahman; Al-Mabrouk , Abdul Hamid Hassan; Ali, Abdalbaki Hassan (Al-Mukhtar Journal of Sciences, 2013)
We studied the effect of temperatures (20c°- 25C°- 30c°- 35c°) and food type (wheat - rice - corn ) and the time (35- 65 -95) day; and combination of these factors on the reproduction rate of the rice weevil Sitophilus oryzae L. The results showed that the best reproduction rate of rice weevil (S.oryzae) was on the rice and, the best temperature for the reproduction for the rice weevil was 20°C and 30°C followed by 25°C on the rice but 35°C was the lethal temperature for rice weevil.